Developing A Control Protocol Algorithm For Stimulating The Street Light System - Wong, Kwo Yiang (Universiti Sains Malaysia, 2017)
This thesis presents the design of the smart protocol algorithms for simulating and controlling the residential street light. The automatic street lighting system will provide a clear and safe environment to the residential area. Based on the previous research and previous works, the automatic street lighting system is only considered by using Light Dependent Resistor (LDR) to activate the system. The previous system only considers the time to activate the street light system and less focus on how to control the street light for each street and junction in the residential area. At the same time, there is no stated or predefined algorithm structure used for the street light control. Thus, smart protocol algorithm is developed to replace the previous system. The new design of the street light system will be stimulated to control the street lights more junctions and streets based on the presence of the residents and vehicles by using infrared sensors. The final prototype is developed by using the control protocol algorithm to activate the system and control all the street lights simultaneously based on the presence of objects. The street light system prototype is tested to be well-developed and well-functioned by applying a few type of conditions and cases.